2014
DOI: 10.1186/1471-2415-14-33
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and tissue inhibitors of metalloproteinases in the aqueous humour of patients with primary angle closure glaucoma - a quantitative study

Abstract: BackgroundAltered levels of specific matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in the aqueous humour of primary open-angle glaucoma (POAG) eyes have been described. In this study, levels of specific MMPs and TIMPs in the aqueous humour of primary angle-closure glaucoma (PACG) eyes were measured and compared with those of POAG as well as non-glaucoma control eyes.MethodsAqueous humour from 16 PACG, 28 POAG and 27 control eyes were sampled during intraocular surgery. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 16 publications
1
25
0
7
Order By: Relevance
“…The estimated sample size for the study was calculated from the mean total protein in controls (0.292 6 0.192), POAG (0.578 6 0.360), and PACG (0.426 6 0.126) mg/mL as mentioned in the reference study 27 with a significance level of 5%, power of 90%, and the effect size of 0.27 using G * Power 3.1 software, and was found to be minimum of 44 in each group.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The estimated sample size for the study was calculated from the mean total protein in controls (0.292 6 0.192), POAG (0.578 6 0.360), and PACG (0.426 6 0.126) mg/mL as mentioned in the reference study 27 with a significance level of 5%, power of 90%, and the effect size of 0.27 using G * Power 3.1 software, and was found to be minimum of 44 in each group.…”
Section: Patient Selectionmentioning
confidence: 99%
“…58 , 59 The upregulation of several MMP mRNAs including MMP2 mRNA has been reported in a steroid-induced mouse glaucoma model, 60 and MMP2 was also moderately increased in the TM and aqueous humor of patients with POAG as compared with healthy individuals. 48 , 61 , 62 Furthermore, changes in the balance between proteases and protease inhibitors (TIMP3) may modify choroid thickness. 63 A decrease in choroid thickness is associated with a number of eye disorders including myopia and AMD.…”
Section: Discussionmentioning
confidence: 99%
“…SMOC2 with multiple domains has the potential to act as protease inhibitors 39. The protease/antiprotease imbalance has also been reported as a key factor in abnormal matrix accumulation leading to potential involvement in the pathogenesis of glaucoma 40. It can be suggested that polymorphism in the SMOC2 gene may be associated with low levels of protease inhibitor subsequently resulting in high MMPs.…”
Section: Discussionmentioning
confidence: 99%